ETHNONYMS IN THE SYSTEM OF PROPER NAMES OF LATGALE - Kļavinska, Antra (Via Latgalica, 2013)
Proper names, including ethnonyms (folk, tribal and other ethnic community names), is anessential component of any language lexis, which particularly brightly reveals a variety ofextralinguistic processes.The aim of the paper is to analyze the conformity of ethnonym transonymization (the change of proper name class) and deonymization (the change of proper name intoappellative) in the culture of Latgale, and linguistic techniques and extralinguistic factors.Linguo-culturological approach has been used in the research, and the link between cultural-historical and social processes in the research of linguistic processes has been taken intoaccount. Determining the origin of ancient ethnonyms, the researchers of the Baltic languagesacknowledge a transonymization model typical to the Balts: hydronym → name of region→ ethnonym (Zinkevičius 2005, 186–187). This paper attempts to reveal various ethnonym(denoting mostly foreigners) transonymization models in the system of proper names ofLatgale, nominating motivation, and the types of word-formation.It seems that the ethnonyms that denote the neighbouring nations (Estonians,Lithuanians, Russians) most frequently turn into other proper names. Transonymizationmodels have been identifi ed as follows:1) ethnonym → anthroponym → oikonym (or ethnonym → oikonym → anthroponym),for example, l ī t a u n ī k i ‘the Lithuanians’ → L ī t a u n ī k s ‘a surname’ →L ī t a u n ī k i ‘a village in Preiļi county’;2) ethnonym → microtoponym, for example, ž y d i ‘the Jews’ → Ž y d a p ū r s‘a marsh in Vārkava county’;3) ethnonym → anthroponym, for example, č y g u o n i ‘the Roma people’ →Č y g u o n s ‘a nickname for a dark-haired man’;4) ethnonym (→ oikonym) → ergonym, for example, l a t g a ļ i ‘The Baltic tribe’ →“L a t g a ļ i” ‘a farm in Mērdzene rural municipality of Kārsava county’.Transonymization of ethnonyms in the culture of Latgale is motivated by historicaland social processes. Transonymization processes present the evidence of Latgalians’ stereotypical perception of foreigners, compact settlement of different ethnic groups inLatgale, and historical events.Various types of word-formation are used in the transonymization process:1) semantic, i.e., only the meaning changes, the morphemic system of lexeme is notchanged, for example, ethnonym p o ļ a k i → oikonym P o ļ a k i (→ surname P o ļ a k s(the male singular form of the ethnonym));2) morphological, typically suffixes are added to ethnonyms (sometimes phoneticchanges in the root occur), for example, i g a u n i ‘the Estonians’ → surnames I k a u n ī k s(ikaun-+-nīk-s); I g o v e n s (igov-+ - en-s);3) syntactical, forming compound words, for example, the ethnonym k r ī v i‘the Russians’ has motivated the oikonym K r ī v a s o l a <Krīva sola ‘Russian Village’,K r ī v m a i z e s <Krīvu maizes ‘Russian bread’;4) formation of analytical forms, where one of the components has ethnonymicsemantics and the second component is a nomenclature word (hill, meadow, marsh, lake,etc.), for example, Ž y d a p ū r s ‘Jew’s marsh’, an attributive adjective, for example, avillage M a z i e L ī t a u n ī k i ‘small Lithuanians’, a substantive of other semantics, forexample, a meadow Č i g o n e i c a s j ū s t a ‘Gypsy’s belt’.Proper names of foreign origin motivated by ethnonyms have taken their stableplace in the system of proper names of Latgale, for example, L a t i š i, a village in Pušmucovarural municipality of Cibla civil-parish (in Russian латыши ‘the Latvians’).Proper names of ethnonymic semantics, used to name various phenomena andrealities, are often included in the lexicon of various dialects of Latvian and even otherlanguages. If to assume the fact that ethnonyms are proper names, then it can be concludedthat the appellatives mentioned above have appeared in deonymization process: ethnonym→ appellative. Moreover, the material of Latgalian dialects confirms the existence of deethnonymicproper names, for example, a lot of different realities are associated with theethnonyms denoting Roma people: č y g u o n i ‘participants of masquerade parade’;č y g o n k a 1) a sort of winter apples, the apple of this sort (dark green and red); 2) the railroad;3) achimenes (flower, Achimenes); 4) mushrooms: wild champignon (Rozites caperata) orugly milkcap (Lactarius necator); č y g u o n a s a u l e ‘the moon’. Appellativeness ofethnonyms has an associative character. The names are reflecting the Latgalians’ stereotypicalperception of appearance, occupation, character traits, and traditions of foreigners as alienand different, however, acceptable and assimilable phenomena.